Loss of Interhemispheric Connectivity in Patients with Lacunar Infarction Reflected by Diffusion-Weighted MR Imaging and Single-Photon Emission CT - Ishihara, Makiko; Kumita, Shin-ichiro; Hayashi, Hiromitsu; Kumazaki, Tatsuo (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: Although decreased neuronal connectivity in white matter has been reported to be a key mechanism of vascular dementia, assessment of white matter changes by diffusion-weighted MR imaging in relation to measures of associative function has not been previously addressed. We evaluated the loss of interhemispheric neuronal connectivity in vascular dementia by measuring diffusional anisotropy of the corpus callosum and determining its relationship to the regional cortical activity as reflected by cortical perfusion.METHODS: Nine patients with multiple lacunar infarction and six healthy volunteers (25–35 years old) were examined. We developed a method to determine the active cortical volume (ACV) by masking iodine-123 iodoamphetamine SPECT scans to eliminate the effect of brain atrophy. The anisotropic rate (AR) was calculated as a ratio of two perpendicular diffusion coefficients in diffusion-weighted MR imaging.RESULTS: Compared with the ACVs of the healthy volunteers, there were significant decreases in the ACVs in the frontal associative areas in the patients, and these were significantly correlated with cognitive scores. The frontal ACVs showed good correlations with the AR of the anterior corpus callosum among all participants; however, only insignificant trends toward correlation were observed between these two parameters within the patient group.CONCLUSION: A possible relationship between diffusional anisotropy of the anterior corpus callosum and frontal associative function was suggested; however, an estimation of the decrease in neuronal connectivity in patients with multiple lacunar infarction in terms of the deterioration in diffusional anisotropy requires further documentation.